Kwa Chong Guan [Singapore, Chairman of National Archives Board, Historian] - Guan, Kwa Chong (Institutional Knowledge at Singapore Management University, 2016)
Kwa Chong Guan is a Senior Fellow of S Rajaratnam School of International Studies and was the man who recognised the importance of Oral History Centre and the National Museum. In 1980s, he led the expansion of the old National Museum to its current three museums and their consolidation under the National Heritage Board. He shares with DNA, ISL the importance and functions of archives and offers a glimpse into his career in the public service and Singapore’s history before the era of Sir Stamford Raffles.